Integrating the scientific approach in STEM-Based learning: advancing critical and creative mathematical thinking skills for future-oriented education - Dwi Yulianto (International Journal on Teaching and Learning Mathematics, 2025)
Although STEM education has been proven to enhance scientific literacy, its effectiveness in developing pre-service mathematics teachers’ critical and creative thinking skills remains underexplored. Furthermore, comparative studies on STEM-based scientific learning versus conventional methods in fostering Higher-Order Thinking Skills (HOTS) remain limited, particularly in the context of future-oriented education. This study aims to analyze the impact of STEM-based scientific learning on the critical and creative thinking skills of pre-service mathematics teachers and compare its effectiveness with conventional instruction. A quasi-experimental posttest-only nonequivalent control group design was employed. A total of 52 students were selected through purposive sampling and divided into an experimental group (n=26, STEM-based scientific learning) and a control group (n=26, conventional learning). Critical thinking was assessed using WGCTA, while creative thinking was measured through TTCT, project analysis, and student engagement observations. The MANOVA results confirm that STEM-based scientific learning is significantly more effective than conventional methods, leading to notable improvements in critical and creative thinking skills. Additionally, the experimental group demonstrated more stable performance, as indicated by a lower standard deviation compared to the control group. These findings underscore that integrating STEM-based scientific learning contributes significantly to strengthening HOTS among pre-service mathematics teachers, serving as a valuable reference for curriculum development in future-oriented education.